2015
DOI: 10.1136/inp.h3440
|View full text |Cite
|
Sign up to set email alerts
|

Canine mast cell tumours: decision‐making and treatment

Abstract: Mast cell tumours (MCTs) are common tumours in dogs. They mainly affect the skin, although they can affect other tissues and organs. In recent years, there have been significant advances in predicting skin MCT behaviour and treatment, including the licensing of two tyrosine kinase inhibitors for the treatment of this condition. This article focuses on skin (cutaneous and subcutaneous) MCTs. It summarises current understanding of MCT behaviour, prognosis and treatment, with a particular focus on treatment decis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…Mast cell tumour (MCT) is the most common cutaneous malignancy in dogs ( 1 ). In view of the wide variation in its biological behaviour, many prognostic factors have been proposed and evaluated in an attempt to improve decision making in the management of this neoplasm ( 2 4 ). Among the therapeutic approaches, surgery stands out as the optimal treatment offering the highest rate of cure for most low to intermediate grade MCTs ( 1 , 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mast cell tumour (MCT) is the most common cutaneous malignancy in dogs ( 1 ). In view of the wide variation in its biological behaviour, many prognostic factors have been proposed and evaluated in an attempt to improve decision making in the management of this neoplasm ( 2 4 ). Among the therapeutic approaches, surgery stands out as the optimal treatment offering the highest rate of cure for most low to intermediate grade MCTs ( 1 , 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Aggressive surgical removal of the mast cell tumor and surrounding tissue is generally the treatment of choice [20,21] might be highly effective. Radiation therapy might be highly effective as well as multimodality therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy might be highly effective as well as multimodality therapy. Several different drugs can be used to treat these high-risk patients, including high doses of steroids, traditional chemotherapy (vinblastine, lomustine) or RTK-inhibitors (Palladia, Kinavet) [21]. In some cases, oral toceranib phosphate (Palladia, SU11654) administration applied [22].…”
Section: Introductionmentioning
confidence: 99%
“…8,27,78,83,84 Patient prognosis differs and is dependent on multiple factors, including histologic grade, tumor location, breed, and clinical stage of the disease at the time of diagnosis. 16,[84][85][86][87][88] Although there is no apparent sex predilection, there is evidence that spayed females may have a higher relative risk of developing a mast cell tumor, compared with the likelihood for their sexually intact counterparts. 8,11,83,87 Investigators of a study 8 of dogs examined at the Animal Medical Center in New York reported an OR of 4.11 for spayed females to develop mast cell tumors, compared with the likelihood for sexually intact bitches, although the age at gonadectomy was unknown for that study.…”
Section: Small Animalsmentioning
confidence: 99%